Pour une vision élargie des performances de la filière ostréicole à partir d’une approche en termes de patrimoine - Audrey Rivaud; Clarisse Cazals (Développement Durable et Territoires)
This article deals with the question of the performance of an industry, viewed in its relations with the space and with the time. The purpose, which contributes to the literature relating to the broadening of the performance, is to insist on the variety of constituent elements of the performance on the one hand and on the existence of contradictions between these elements on the other hand. Thus, we assume the diversity of performing production models and we stress the importance to define indicators which take into account this diversity. To this end, the tools developed within the framework of the heritage economy are used. We refer to the case study of oyster-farming industry in the Arcachon Bay (France) to illustrate these points.